PENGEMBANGAN TEKNIK DAN INSTRUMEN ASESMEN ASPEK PENGETAHUAN BERASIS TEKHNOLOGI - afida nurrizqi nurrizqi (Atta'dib Jurnal Pendidikan Agama Islam, 2021)
AbstrakAbstractTechnology and information are growing so rapidly along with the times. In the world of education, this technological development helps teachers in the learning process so that the teaching and learning process can be carried out effectively in order to achieve learning objectives. Technological developments can create a more varied and less boring learning atmosphere. The purposes of the assessment are: keeping track, serves to ensure that teaching and learning activities are in accordance with the initial planning; checking up, namely to find out the difficulties felt by students in the learning process; finding out, looking for and at the same time finding the obstacles experienced during the learning process. Therefore, technology-based assessment instruments have now been developed to make it easier for teachers to assess students. The research method used is library research or often called literature study, which is a series of activities related to the methods of collecting library data, reading and taking notes and processing research materials. Researchers deal directly with text or numerical data and not with direct experience from field studies or eyewitnesses in the form of events, people or other objects, but from libraries that are 'ready to use'. The results of this study indicate that the Development of Techniques and Assessment Instruments from the Technology-Based Knowledge Aspect includes: 1) Google forms 2) Wondershare quiz creator, and 3). That Quiz.Keywords: Assessment, Instrument, Technology.